Low-cost biochar adsorbents prepared from date and delonix regia seeds for heavy metal sorption. (November 2021) - Pal, Dan Bahadur; Singh, Arvind; Jha, Jay Mant; Srivastava, Neha; Hashem, Abeer; Alakeel, Maha Abdullah; Abd_Allah, Elsayed Fathi; Gupta, Vijai Kumar
Graphical abstract: Highlights: Low cost biochar adsorbents prepared from Date and Delonix regia seeds. The removal efficiency of As with Date seed biochar was achieved to 95% in 1 h. The maximum adsorption capacity of Delonix regia seed was 6.2 mg.g −1 . Abstract: In this study, low-cost biochar as bio-adsorbents derived from locally accessible delonix regia seed and date seeds were explored for heavy metal environmental cleaning. These prepared biochars were characterized by proximate and elemental analyses, CHNS/O analysis, Fourier-transformed infrared spectroscopy and thermo-gravitational methods. Bio-sorbent's ability to adsorb arsenic ions in synthetic wastewater was studied and optimized at varying solution pH, adsorbent dose, and starting metal concentrations. Experimentation and optimization studies were also carried out with the help of Design-software 6.0.8. The trials were designed by using response-surface methods, which includes three components and stages of Box-Behnken design. Date seeds derived-biochars eliminated 95% of arsenic from synthetic wastewater, whereas Delonix regia seeds removed 93.8%. The kinetics, isotherms and mechanism of As adsorption were also postulated. This study proposes that these seed's biochars might be employed as an effective, low-cost, and environmentally friendly adsorbent to remove heavy metals from the environment.